Salmonella enterica Optimizes Metabolism After Addition of Acyl-Homoserine Lactone Under Anaerobic Conditions - Carneiro, Deisy G.; Almeida, Felipe A.; Aguilar, Ananda P.; Vieira, Nívea M.; Pinto, Uelinton M.; Mendes, Tiago A. O.; Vanetti, Maria Cristina D. (Frontiers in Microbiology, 2020)
Acyl-homoserine lactones (AHLs) are quorum sensing (QS) signaling molecules that mediate cell-to-cell communication in Gram-negative bacteria. Salmonella does not produce AHL however, it is able to recognize AHLs produced by other species through SdiA protein and modulates important cellular functions. In this work, the influence of the N-dodecanoyl-DL-homoserine lactone (C12-HSL) on glucose consumption, metabolic profile, and the gene expression of Salmonella throughout the cultivation time in Tryptic Soy Broth (TSB) under anaerobic conditions was evaluated. Analysis of the supernatant culture in high-performance liquid chromatography (HPLC) revealed lower glucose uptake after 4 and 6 h of the addition of C12-HSL. Gas chromatography-mass spectrometry (GC-MS) based analysis of the intracellular metabolites revealed C12-HSL perturbation in the abundance levels of metabolites related to the metabolic pathways of glycerolipids, purines, amino acids, and aminoacyl-tRNA biosynthesis. The real-time quantitative PCR (RT-qPCR) indicated that Salmonella increase expression of genes associated with nucleoside degradation and quantification of metabolites supported the induction of pentose phosphate pathway to ensure growth under lower glucose consumption. The data obtained suggest an important role of C12-HSL in the adjustment for optimization of metabolism in a situation of high population densities.